A novel test configuration designed for investigating mixed mode II/III fracture. (15th June 2018) - Saboori, Behnam; Ayatollahi, Majid R.
Highlights: A novel test configuration was proposed for exploring mixed mode II/III fracture. The test configuration can cover the full range of mixed mode II/III loading. The test rig advantages are simplicity and convenience of test sample preparation. Other advantages of the test setup are low cost and ease of utilization. Finite element analysis verified the effectiveness of the designed configuration. Abstract: In this paper, a novel test setup is introduced to investigate mixed mode II/III fracture (fracture under combined in-plane and out-of-plane shear loadings) in components weakened by crack. The designed loading fixture can exert the full range of mixed mode II/III loading conditions, from pure mode II to pure mode III, to a single edge cracked test specimen. The proposed test rig has a simple configuration as well as a low manufacturing cost and it is easy to be utilized and installed in conventional loading machines for performing fracture experiments. Three-dimensional finite element analysis has been employed for evaluating the performance and effectiveness of the test configuration in different mixed mode loading cases. The computational results demonstrate that the designed loading apparatus can appropriately create various mode mixities from pure mode II to pure mode III and is capable of assessing the mode II/III fracture behaviour of the materials experimentally.